Bis(merocyanine) Homo‐Folda‐Dimers: Evaluation of Electronic and Spectral Changes in Well‐Defined Dye Aggregate Geometries. Issue 48 (5th August 2019) - Kirchner, Eva; Bialas, David; Wehner, Marius; Schmidt, David; Würthner, Frank
Abstract: A series of three bis(merocyanine) dyes comprising chromophores of different conjugation lengths has been synthesized and the intramolecular aggregation process was investigated by UV/Vis absorption spectroscopy. The spectral changes observed upon variation of the solvent polarity reveal a folding process resulting in a cofacial π‐stack of two chromophores with a decrease of the aggregation tendency with increasing chromophore length and solvent polarity. Solvent‐dependent UV/Vis studies of the monomeric reference dyes show a significant increase of the polyene‐like character for dyes with longer polymethine chains in nonpolar solvents, which is reversed upon aggregation due to the polarizability effect of the adjacent chromophore within the dye stack. The pronounced hypsochromic shift of the absorption band observed upon aggregation indicates strong coupling of the dyes' transition dipole moments, which was confirmed by quantum‐chemical analysis. Abstract : Facing stacks : Folding of three bis(merocyanine) dyes comprising chromophores of different conjugation lengths leads to cofacial π‐stacks of two chromophores. Hence, detailed studies on the electronic and spectral changes of the chromophores upon aggregation are enabled.